Domestic Trends in the United States, China, and Iran Implications for U.S. Navy Strategic Planning - Gordon, John IV (RAND Corporation, 2008)
The U.S. Navy faces uncertainty about the degree to which it will have to prepare for a high-end future conflict versus the so-called Long War. To help the Navy understand how critical near-, mid-, and far-term trends in the United States, China, and Iran might influence U.S. security decisions in general and the Navy's investments in particular, RAND examined emerging domestic and regional nonmilitary trends in each of the three countries.